Leases of low-value assets: how are companies and jurisdictions approaching the lack of guidance in IFRS 16? - Rocha, Marcelo De Grande (2022)
This research investigates how entities address the absence of a definition for low-value assets in IFRS 16. We developed four strategies to collect and analyze data. First, we performed a content analysis on the comment letters (CL) to the IASB’s 2013 Exposure Draft (ED), aiming to find the origins of the exemption. Secondly, we applied a survey with jurisdictional authorities from countries that use IFRS, aiming to learn how they have regulated the low-value assets. Then, we performed a content analysis on the 2020 Financial Statements (FS) published by the Brazilian companies, aiming to identify how they implemented the exemption, and how auditors reacted. Finally, we applied a survey with Brazilian practitioners aiming to fulfill the gaps left by the notes. The main conclusion of our research shows that the IASB did not apply appropriate concepts to justify lease accounting requirements for the concept of the low-value asset. Especially its contradiction to the concept of Materiality, which is an entity-specific fundamental qualitative characteristic of relevance. On the other hand, the assessment of whether an underlying asset is of low value is not affected by the size, nature or circumstances of the lessee. The analysis of CL on the ED 2013 enabled the understanding of the concept. The content analysis of FS and survey shows that IFRS 16 - Leases were implemented by a large majority of the Brazilian companies. The results of both methodologies also show that 96% of lessees use a quantitative threshold to operationalize the concept, and 61% of archival analyzed companies used the exemption in December 2020. The majority of Companies in Brazil did not disclose the expense relating of low-value assets. This is the first study to approach the concept of low-value from IFRS16 and we expect that the knowledge gained from this research might be a relevant input to the IASB to the post-implementation review of the IFRS 16 and the revision of Practice Statement number 2 – Making Materiality Judgement.